'They won't change it back in their heads that we're trash': the intersection of sex work‐related stigma and evolving policing strategies. Issue 7 (26th April 2016) - Krüsi, Andrea; Kerr, Thomas; Taylor, Christina; Rhodes, Tim; Shannon, Kate
Abstract: In Vancouver, Canada, there has been a continuous shift in the policing of sex work away from arresting sex workers, which led to the implementation of a policing strategy that explicitly prioritised the safety of sex workers and continued to target sex workers' clients. We conducted semi‐structured interviews with 26 cisgender and five transgender women street‐based sex workers about their working conditions. Data were analysed thematically and by drawing on concepts of structural stigma and vulnerability. Our results indicated that despite police rhetoric of prioritising the safety of sex workers, participants were denied their citizenship rights for police protection by virtue of their 'risky' occupation and were thus responsiblised for sex work related violence. Our findings further suggest that sex workers' interactions with neighbourhood residents were predominantly shaped by a discourse of sex workers as a 'risky' presence in the urban landscape and police took swift action in removing sex workers in the case of complaints. This study highlights that intersecting regimes of stigmatisation and criminalisation continued to undermine sex workers citizenship rights to police protection and legal recourse and perpetuated labour conditions that render sex workers at increased risk for violence and poor health.